Urinary sodium excretion is low prior to acute kidney injury in patients in the intensive care unit - de Morais, David Gomes; Sanches, Talita Rojas Cunha; Santinho, Mirela Aparecida Rodrigues; Yada, Eduardo Yuki; Segura, Gabriela Cardoso; Lowe, Diogo; Navarro, Guilherme; Seabra, Victor Faria; Taniguchi, Leandro Utino; Malbouisson, Luiz Marcelo Sá; de André, Carmen Diva Saldiva; Andrade, Lúcia; et al. (Frontiers in Nephrology, 2022)
Background The incidence of acute kidney injury (AKI) is high in intensive care units (ICUs), and a better understanding of AKI is needed. Early chronic kidney disease is associated with urinary concentration inability and AKI recovery with increased urinary solutes in humans. Whether the inability of the kidneys to concentrate urine and excrete solutes at appropriate levels could occur prior to the diagnosis of AKI is still uncertain, and the associated mechanisms have not been studied. Methods In this single-center prospective observational study, high AKI risk in ICU patients was followed up for 7 days or until ICU discharge. They were grouped as “AKI” or “No AKI” according to their AKI status throughout admission. We collected daily urine samples to measure solute concentrations and osmolality. Data were analyzed 1 day before AKI, or from the first to the fifth day of admission in the “No AKI” group. We used logistic regression models to evaluate the influence of the variables on future AKI diagnosis. The expression of kidney transporters in urine was evaluated by Western blotting. Results We identified 29 patients as “No AKI” and 23 patients as “AKI,” the latter being mostly low severity AKI. Urinary sodium excretion was lower in “AKI” patients prior to AKI diagnosis, particularly in septic patients. The expression of Na+/H+ exchanger (NHE3), a urinary sodium transporter, was higher in “AKI” patients. Conclusions Urinary sodium excretion is low before an AKI episode in ICU patients, and high expressions of proximal tubule sodium transporters might contribute to this.